Peran Etnomatematika dalam Meningkatkan Kemampuan Higher order thinking skills Siswa pada Pembelajaran Matematika - Ahmad Faqihi; Ruslin Ruslin; Chairul Aly Ramli (Mandalika Mathematics and Educations Journal, 2026)
Higher-Order Thinking Skills (HOTS) are a crucial competency in 21st-century mathematics education; however, proficiency levels remain low because instruction tends to be procedure-oriented and lacks contextual relevance. One approach capable of addressing this issue is ethnomathematics—an instructional method that integrates local culture into mathematics learning. This study aims to analyze research trends, the role of ethnomathematics in enhancing HOTS, implementation methods, and factors influencing the effectiveness of its application. A literature review methodology was employed, analyzing national and international scholarly articles published between 2020 and 2026. Data analysis involved identification, selection, content analysis, and synthesis. The findings indicate that ethnomathematics research trends have evolved from merely exploring mathematical concepts within culture to implementing ethnomathematics as an innovative instructional approach integrated with various learning models. Ethnomathematics has proven effective in enhancing problem-solving skills, critical thinking, creative thinking, mathematical reasoning, numeracy literacy, and computational thinking. Its implementation is achieved by utilizing various elements of local culture as learning contexts.